A meta-analysis of surgical margin status and prognosis after precise resection of liver cancer using fluorescence imaging-guided surgery - Fang Xie; Qian Zhang; Yuming Jia; Kaijian Lei; Hongru Yu; Wei Zhang; Li Li; Daohong Kan (Photodiagnosis and Photodynamic Therapy)
Background: The aim of this study is to evaluate the value of intraoperative fluorescence imaging in assisting tumor localization and margin delineation during liver resection surgery, with the goal of improving the negative surgical margin rate and overall margin status. Methods: A systematic search was conducted in the PubMed, Web of Science, Embase, and Cochrane Library databases for studies on the use of fluorescence imaging to aid in tumor localization and margin detection in liver cancer published between their inception and March 2025. After quality assessment of the included studies, a meta-analysis was performed using the STATA/SE 12.0 statistical software. Results: A total of 10 studies comprising 1097 patients were included in this meta-analysis. Compared to conventional liver resection, fluorescence-guided hepatectomy significantly increased the R0 resection rate [Odds ratio (OR) = 2.51, 95 % confidence intervals (CI): 1.65, 3.81, P = 0.000], with similar results observed in subgroup analyses. In addition, the fluorescence-guided hepatectomy group showed significantly less intraoperative blood loss [Weighted mean differences (WMD) = -100.53, 95 % CI:171.38, -29.68, P = 0.005]. However, no statistically significant differences were observed between the two groups in terms of margin distance, operative time, intraoperative transfusion, hospital stay, or overall complication rate. Conclusion: Fluorescence-guided hepatectomy can effectively increase the R0 resection rate and may contribute to reducing postoperative recurrence of liver cancer. However, further multicenter randomized controlled trials with larger sample sizes are needed to validate its impact on margin distance, operative time, intraoperative transfusion, hospital stay, and complication rates.